Agency hazards and alliance portfolios - Reuer, Jeffrey J.; Ragozzino, Roberto (Strategic Management Journal, 2005)
Prior research over several decades has catalogued many positive motives underlying firms' decisions to engage in joint ventures and other forms of alliances. In this empirical analysis, we investigate whether agency problems brought about by the separation of ownership and control also stimulate the development of firms' joint venture portfolios. By focusing on joint ventures, as opposed to diversification in general or acquisitions, we address the recent debate on agency theory's domain. Results from a sample of U.S. manufacturing firms' alliance portfolios offer supporting evidence, and comparable findings are obtained for international and domestic joint ventures. Agency hazards are also found to bring about extensions of firms' nonequity alliance portfolios in both the international and domestic settings. Copyright © 2005 John Wiley & Sons, Ltd.